KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN NASABAH PADA BMT BAROKATUL UMMAH DI KABUPATEN MERAUKE - Orin Ramadani; Abdul Rahman Kadir; Abdullah Sanusi (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study using quantitative descriptive research that is to know the Quality of Service In Improving Customer Satisfaction. While the survey was conducted on the customers at BMT Barokatul Ummah in Merauke District. The results of this study indicate that all aspects of Assurance, Reliability, Tangible, and Responsiveness dimensions have been well executed, and have a positive and significant impact on customer satisfaction on BMT Barokatul Ummah. This means that the increased dimensions Assurance, Reliability, Tangible, and Responsiveness the higher the customer satisfaction. While Compliance dimenis has a negative and significant impact on customer satisfaction. This means that if the dimensions of Compliance actually implemented according to Islamic Shari'a on BMT Barokatul Ummah, then the level of customer satisfaction will decrease. And for Empathy dimension has negative and insignificant effect to customer satisfaction. This means that the Empathy dimension does not affect customer satisfaction in BMT Barokatul Ummah in Merauke Regency.